2016
DOI: 10.1016/j.agee.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excluding grazing on the vegetation and soils of degraded sparse-elm grassland in the Horqin Sandy Land, China

Abstract: 32Livestock grazing is a crucial cause of vegetation degradation and desertification in sandy lands. 33The sparse-elm grassland of Horqin Sandy Land, China has suffered severe degradation of 34 biodiversity and ecosystem services. Management to exclude grazing is often necessary for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…Moreover, the existing sole studied on the effectiveness of established EXs to improve soil carbon stock potential was inconsistent and variable (Piñeiro et al 2010;Raiesi and Riahi 2014;Aynekulu et al 2017). For instance, in some studies reported that EXs improves the carbon stock potential (e.g., Shrestha and Stahl 2008;Mureithi et al 2014;Yimer et al 2015) and several other observes decreases (e.g., Reid et al 2004;Mekuria et al 2017, Tang et al 2016 while Aynekulu et al (2017) and Mekuria et al (2014) reported that EXs did not influence soil organic carbon. SOC increased in the EXs, because grazing is one of the critical factors in species composition and grassland degradation that have a significant effect on carbon storage (Piñeiro et al 2010: Wu et al 2014Raiesi and Riahi 2014;Yimer et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existing sole studied on the effectiveness of established EXs to improve soil carbon stock potential was inconsistent and variable (Piñeiro et al 2010;Raiesi and Riahi 2014;Aynekulu et al 2017). For instance, in some studies reported that EXs improves the carbon stock potential (e.g., Shrestha and Stahl 2008;Mureithi et al 2014;Yimer et al 2015) and several other observes decreases (e.g., Reid et al 2004;Mekuria et al 2017, Tang et al 2016 while Aynekulu et al (2017) and Mekuria et al (2014) reported that EXs did not influence soil organic carbon. SOC increased in the EXs, because grazing is one of the critical factors in species composition and grassland degradation that have a significant effect on carbon storage (Piñeiro et al 2010: Wu et al 2014Raiesi and Riahi 2014;Yimer et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Le Houérou (1995) stressed that the vegetation in these arid regions has adapted to recurrent drought conditions over centuries and past millennia acquiring an ability to recover their characteristics after disturbance. Similarly, Tang et al (2016) suggested that livestock exclusion can safeguards rangeland from livestock-induced disturbances and accelerate the recovery of degraded pasture species.…”
Section: Effects Of Sheep Exclusion On Overall Alpha Diversities and mentioning
confidence: 99%
“…Improving grazing management practices is viewed as a fundamental approach to restore degraded rangelands ( Mekuria andAynekulu 2011, Jones 2013). A variety of management strategies have been implemented to restore degraded rangelands worldwide (Neffar et al 2018), but the most fundamental and economic management practice remain a nature-based solution "grazing exclusion", especially in arid and semiarid regions (Tang et al 2016), due to its low investment, extensiveness, simple implementation, and quick response .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1990s, land reclamation and livestock grazing have been widely conducted in arid and semi-arid lands of China (Stumpp et al, 2005;Tang et al, 2016;Jia et al, 2018), thus causing vegetation destruction and desertification (Zheng et al, 2003;Wang et al, 2004;Yan et al, 2016). Hence, it is essential to take measures to recover the damaged land in these areas.…”
Section: Introductionmentioning
confidence: 99%